SOSIALISASI DAN PELATIHAN PEMBUATAN PAKAN BERNUTRISI DENGAN METODE FERMENTASI RUMPUT GAJAH SEBAGAI UPAYA PENINGKATAN KUALITAS HEWAN TERNAK DI DESA BOROK TOYANG - Mara, I Made; Sasono, Marendra; Pramana, Yoga Tri; Fitri, Imayatul; Handayani, Fitri; Pratama, Imam Akbar; Firdaus, Muhammad; Islami, Nurul Hida Wahyuni; Paramitha, Ni Ketut Rizka Widya; Saputri, Lia; Musyahadati, Shufi (Universitas Mataram, 2025)
Borok Toyang Village, located in the West Sakra District, East Lombok Regency, has a very high potential for livestock farming, especially cattle and goats. However, farmers still face difficulties in providing high-quality feed for their livestock to ensure optimal growth and productivity. The traditional feed used reduces livestock growth and increases production costs. To address this issue, the socialization of elephant grass fermentation, a better livestock feed innovation, was carried out. This activity involves initial observation, socialization, and direct training for farmers in Borok Toyang Village. Observation was conducted to determine the condition of the farms and the feeding patterns. The training included the direct preparation of fermented feed, and socialization was provided through seminars and open discussions about the benefits of fermentation. The results of the activities show that farmers have a better understanding of the importance of innovation in providing livestock feed. It has been proven that the fermentation of elephant grass accelerates livestock growth, improves the nutritional quality of feed, and reduces dependence on expensive commercial feed. Additionally, this method helps ensure the availability of quality feed, especially during the dry season. Some farmers have expressed interest in adopting this method independently and plan to form small groups to share experiences in its implementation. Farmers in Borok Toyang Village hope to independently produce more livestock, reduce production costs, and enhance the village's economic resilience through livestock farming with this socialization and training.